OPTIMALISASI SUMBER DAYA ALAM MENUJU PEMBANGUNAN EKONOMI DAN KESEJAHTERAAN MASYARAKAT DI WILAYAH PERBATASAN - Mayasuri Presilla (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2011)
Abstract: A border region is a leading point of one country against another country. The border region needs special attention and priority from central as well as local governments as there are considerable issues sunound it. One crucial thing that should be the main focus in the border region is the issue of economic development and local communities' welfare. Data used in this paper is mainly based on the field research in Nunukan District, East Kalimantan Province in 2010. The discussion in this paper is emphasized on the development of local natural resources for achievingeconomic development and the welfare of local people in Nunukan District